Analisis Strategi Pengembangan Kerajinan Tangan Noken dalam Rangka Meningkatkan Pendapatan Keluarga Orang Asli Papua (OAP) di Kota Jayapura - Pallo, Luciana Imanuella (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
This study aims to analyze the role of female noken craftspeople in fulfilling the socio-economic needs of Indigenous Papuan (OAP) families in Jayapura City, to identify the constraints faced by these craftspeople, and to formulate empowerment strategies that can help improve their economic capacity, particularly in terms of access to capital, raw materials, skills training, and technology-based marketing. To achieve these objectives, this study employed a qualitative research method. Data collection techniques included in-depth interviews with eight noken craftspeople as informants, direct observation at selling locations such as Hamadi Market, Padang Bulan, and Lingkaran Abe, as well as secondary data collection from policy documents and previous studies. The data analysis method adopted the technique from Miles and Huberman, which consists of three stages: data reduction, data display, and conclusion drawing or verification. The results showed that female noken craftspeople play a crucial role as both family income providers and cultural preservers, yet their earnings remain low, ranging from IDR 100,000 to IDR 500,000 per month. The main constraints include difficulties in obtaining quality raw materials that must be ordered from villages with a waiting time of up to two months, high operational costs for stall rental and transportation, challenges in attracting stable customers, and a lack of tangible support from the government, the Cooperative and SME Office, mass media, and universities. The craftspeople hope to receive assistance with raw materials, decent selling spaces, participation in festivals, capital support, and greater attention from the government. This study concludes that a comprehensive empowerment strategy is needed through collaboration among craftspeople, the government, the private sector, and the community to increase Indigenous Papuan family income and sustainably preserve the cultural heritage of noken. Keywords: Noken, Development Strategy, Women's Empowerment, Family Income, Indigenous Papuan (OAP)